MicroRNAs reshape the immunity of insects in response to bacterial infection - Abbas, Muhammad Nadeem; Kausar, Saima; Asma, Bibi; Ran, Wenhao; Li, Jingui; Lin, Zini; Li, Tiejun; Cui, Hongjuan (Frontiers in Immunology, 2023)
The interaction between bacteria and insects can significantly impact a wide range of different areas because bacteria and insects are widely distributed around the globe. The bacterial-insect interactions have the potential to directly affect human health since insects are vectors for disease transmission, and their interactions can also have economic consequences. In addition, they have been linked to high mortality rates in economically important insects, resulting in substantial economic losses. MicroRNAs (miRNAs) are types of non-coding RNAs involved in regulating gene expression post-transcriptionally. The length of miRNAs ranges from 19 to 22 nucleotides. MiRNAs, in addition to their ability to exhibit dynamic expression patterns, have a diverse range of targets. This enables them to govern various physiological activities in insects, like innate immune responses. Increasing evidence suggests that miRNAs have a crucial biological role in bacterial infection by influencing immune responses and other mechanisms for resistance. This review focuses on some of the most recent and exciting discoveries made in recent years, including the correlation between the dysregulation of miRNA expression in the context of bacterial infection and the progression of the infection. Furthermore, it describes how they profoundly impact the immune responses of the host by targeting the Toll, IMD, and JNK signaling pathways. It also emphasizes the biological function of miRNAs in regulating immune responses in insects. Finally, it also discusses current knowledge gaps about the function of miRNAs in insect immunity, in addition to areas that require more research in the future.